Ice(berg) Transport Costs - Maarten Bosker; Eltjo Buringh (Center for Economic Studies and ifo Institute (CESifo), 2018)
Iceberg transport costs are one of the main ingredients of modern trade and economic geography models: transport costs are modelled by assuming that a fraction of the goods shipped “melts in transit”. In this paper, we investigate whether the iceberg assumption applies to the costs of transporting the only good that literally melts in transit: ice. Using detailed information on Boston's nineteenth-century global ice trade, we show that ice(berg) transport costs in practice were a combination of a true ad-valorem iceberg cost: melt in transit, and freight, (off)loading and insurance costs. The physics of the melt process and the practice of insulating the ice in transit imply an immediate violation of the iceberg assumption: shipping ice is subject to economies scale.
Keywords: F10; N70; N51; 330; iceberg transport costs; nineteenth-century Boston ice trade